The Epidermis and the Respiratory Tract as Bioassay Systems in Tobacco Carcinogenesis* - Wynder, E. L. (Nature Publishing Group, 1970)
In tobacco carcinogenesis research, considerable attention has been paid to the choice of the bioassay. The ideal system should simulate the human smoking setting as closely as possible and should utilize tissue of a type similar to that found at the sites where the tobacco smoke-related cancers originate in man. However, although certain inhalation experiments in the laboratory meet these requirements to some extent, they are generally timeconsuming and difficult to evaluate and since they usually have to be performed on large animals, are extremely costly when used for the identification of the actual tumorigenic agents in the smoke. The present article examines the reasons why mouse skin is a useful bioassay. The system has enabled investigators to identify tumour initiators and accelerators and to determine that the major tumour promoters reside in the weakly acidic portion of tobacco smoke. The mouse skin bioassay demonstrated that with significant inhibition of the pyrosynthesis of alkylated and non-alkylated polynuclear aromatic hydrocarbons, the tumorigenicity of the “tar” will also decrease significantly. IMAGES: